3D printed polycaprolactone/beta-tricalcium phosphate/magnesium peroxide oxygen releasing scaffold enhances osteogenesis and implanted BMSCs survival in repairing the large bone defect. Issue 28 (5th July 2021) - Peng, Ziyue; Wang, Chengqiang; Liu, Chun; Xu, Haixia; Wang, Yihan; Liu, Yang; Hu, Yunteng; Li, Jianjun; Jin, Yanglei; Jiang, Cong; Liu, Liangle; Guo, Jiasong; et al.
Abstract : Fabricate a MgO2 -contained scaffold by 3D printing to improve ischemia and hypoxia in bone defect area. Abstract : Ischemia and hypoxia in the bone defect area remain an intractable problem when treating large bone defects. Thus, oxygen-releasing biomaterials have been widely researched in recent years. Magnesium peroxide (MgO2 ) can release oxygen (O2 ), and magnesium ions (Mg 2+ ), simultaneously, which is seen to have significant potential in bone substitutes. In this study, we used 3D printing technology to fabricate a MgO2 -contained composite scaffold, which was composed of polycaprolactone (PCL), beta-tricalcium phosphate (β-TCP) and magnesium peroxide (MgO2 ). Physical properties and O2 /Mg 2+ releasing behavior of the scaffold were studied. Then, we evaluated the effects of the scaffold on cell survival, proliferation, migration, adhesion and osteogenic differentiation by the co-culture of bone marrow mesenchymal stem cells (BMSCs) and scaffold under normoxia and hypoxia in vitro . Finally, the osteogenic properties of the scaffold in vivo were evaluated via the rat femoral condylar bone defect model. The PCL/β-TCP/MgO2 scaffold showed good mechanical properties and sustained O2 and Mg 2+ release for about three weeks. Meanwhile, the scaffold showed appreciable promotion on the survival, proliferation, migration and osteogenic differentiation of BMSCs under hypoxia compared with control groups. The results of imaging studies and histological analysis showed that implantation of PCL/β-TCP/MgO2 scaffold could promote seed cell survival and significantly increased new bone formation. In sum, the PCL/β-TCP/MgO2 scaffold is promising with great potential for treating large bone defects.